ANALYSIS OF TEACHER CERTIFICATION AND WORK CLIMATE ON TEACHER JOB SATISFACTION THROUGH MOTIVATION AT STATE VOCATIONAL SCHOOL 1 BENER MERIAH - Muazimah; Kiki Farida Ferine; Elfitra Desy Surya (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the influence of teacher certification and work climate on teacher job satisfaction through motivation as an intervening variable at SMK Negeri 1 Bener Meriah. The background of this study is based on the importance of job satisfaction in improving the quality of learning, which is influenced by internal and external factors such as professional certification, work environment, and motivation. This study uses a quantitative approach with a population of 74 teachers, all of whom are sampled (saturated sample). The data analysis technique uses Partial Least Square (PLS) through SmartPLS software. The results of the study indicate that: (1) teacher certification has a positive and significant effect on job satisfaction and motivation; (2) work climate has a positive and significant effect on job satisfaction and motivation; (3) motivation has a positive and significant effect on job satisfaction; and (4) motivation significantly mediates the effect of teacher certification and work climate on job satisfaction. These findings emphasize the important role of motivation in strengthening the influence of certification and work climate on teacher job satisfaction.